2020
DOI: 10.1002/jum.15482
|View full text |Cite
|
Sign up to set email alerts
|

Elastography for Pediatric Chronic Liver Disease

Abstract: In adults with chronic liver diseases, ultrasound and magnetic resonance shear wave elastography (SWE) can replace liver biopsy in several clinical scenarios. Several guidelines on the use of ultrasound SWE for the adult population have been published. However, the number of publications in the pediatric population is limited, and available guidelines on SWE do not specifically address pediatric chronic liver diseases. In this article, we review the literature on the use of SWE for pediatric chronic liver dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 113 publications
0
31
0
Order By: Relevance
“…In phantom studies, it has been shown that the readings with the higher frequency of the linear transducer are higher than those obtained with the convex transducer. Moreover, in children the acquisition could be more challenging due to the lack of cooperation and this could affect the feasibility of the technique [30,31].…”
Section: Arfi-based Techniques: Transducer (Frequency) Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In phantom studies, it has been shown that the readings with the higher frequency of the linear transducer are higher than those obtained with the convex transducer. Moreover, in children the acquisition could be more challenging due to the lack of cooperation and this could affect the feasibility of the technique [30,31].…”
Section: Arfi-based Techniques: Transducer (Frequency) Selectionmentioning
confidence: 99%
“…Before launching the acquisition, the operator asks the patient to hold the breath in a neutral position without performing a Valsalva's maneuver for the few seconds needed for the acquisition [15]. Special applications in pediatric patients are discussed elsewhere [30,31,53].…”
Section: How To Use Shear Wave Elastographymentioning
confidence: 99%
See 1 more Smart Citation
“…He had a waxing and waning course of hepatitis for the first six months after initial therapy. This was accompanied by increased liver stiffness on ultrasound elastography, which can indicate inflammation in the acute setting and fibrosis in the chronic setting 18,19 . MRCP showed narrowing of the common hepatic bile duct and dilation of the intrahepatic bile ducts.…”
Section: Results: Case Descriptionmentioning
confidence: 98%
“…In this study, we evaluated a consecutive cohort of difficult patients in a nonacademic outpatient setting to determine the time to perform the examination and determine the range of LS, attenuation coefficient, and shear wave dispersion slopes by US. SWE is maturing with several organizations providing recommendations for performing and interpreting LS results [7,[24][25][26][27][28]. Guidelines have recommended not using Metavir cut-off values but the probability of cACLD as this is what is clinically important as these are the patients who are at risk for the complications of CLD including portal hypertension, liver failure, and hepatocellular carcinoma [22].…”
Section: Discussionmentioning
confidence: 99%